2013
DOI: 10.4028/www.scientific.net/amr.856.257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Physical and Mechanical Properties of Ceramic Tiles Processed Using Steel Slag

Abstract: This present study has evaluated the physical and mechanical properties of ceramic tiles processed from steel slag. The chemical compositions of both samples were conducted using atomic absorption spectrophotometer (AAS). Steel slag in the range of 0-100wt% was added to kaolinite clay. The blended samples were hydraulic pressed into rectangular moulds, oven dried and sintered within the temperature range of 1100°C - 1200°C. Surface appearance and colouration of sintered products were observed. Linear shrinkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…However, its market competitiveness of glass ceramics is not strong due to its complex process and high energy consumption. Chukwudi et al [9] studied the sintering properties of the materials with kaolinite, clay and steel slag as aggregates and the results showed that the ceramic bricks prepared with 20%-60% steel slag had good properties. Zong [10] et al prepared high value-added ceramics with steel slag and chemical substances such as SiO 2 and MgO as raw materials, but the content of steel slag was less than 30%.…”
Section: Introductionmentioning
confidence: 99%
“…However, its market competitiveness of glass ceramics is not strong due to its complex process and high energy consumption. Chukwudi et al [9] studied the sintering properties of the materials with kaolinite, clay and steel slag as aggregates and the results showed that the ceramic bricks prepared with 20%-60% steel slag had good properties. Zong [10] et al prepared high value-added ceramics with steel slag and chemical substances such as SiO 2 and MgO as raw materials, but the content of steel slag was less than 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Beshr et al [15] compared how the compressive strength, tensile strength and elastic modulus of high-strength concrete are affected by four coarse aggregates, namely, limestone, dolomite, quartzite and steel slag. Chukwudi and Okorie [16] treated ceramic tiles with kaolinite clay and steel slag, revealing that the sample tiles containing 20-60wt% steel slag have good performance.…”
Section: Introductionmentioning
confidence: 99%